(untitled) (International Journal of Built Environment and Sustainability, 2022)
The street is a vital public space for all in a city. It is the spine that connects to buildings, transportation nodes, public spaces like pocket spaces and other nodes for pedestrian. Sustainable Development Goals (SDGs) promotes the inclusivity for all. To achieve sustainability, street should be safe for all especially women who are a vulnerable group. As a public space, there are many restrictions implemented during the Movement Control Order (MCO) to curb the spread of Covid-19, therefore the livelihood, dynamic and safety is a concern for those who still needs to be on the street. Even though the city street is not as busy as before the pandemic, safety is still a main concern especially amongst women. This study is focusing on women’s perception of safety in the street. This is always a concern as the pandemic has affected the economic sectors which in turn affects employment. Unemployment leads to crime which creates an unsafe perception. In order to evaluate the issue, a case study approach has been chosen and Jalan Tuanku Abdul Rahman in Kuala Lumpur is the area for this study. This study was performed through mixed method of in-depth interview, structured observation and questionnaire survey. Finding reveals that to enhance perception of safety for women, street design needs to consider both physical and social characteristic in the city. Pedestrian needs to use the street during the pandemic, and therefore findings from this study could assist policy maker and designer in developing framework for a safer street